PENINGKATAN HASIL PANEN IKAN NILA DENGAN METODE PENYEMPROTAN AIR - Sunardi Sunardi; Tri Wahyono; Fitroh Anugrah Kusuma Yudha (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
Rowo Jombor, apart from being used to irrigate rice field, also has potential as a tourist spot and fish farming. Currently, Rowo Jombor fish farmers are experiencing problems of lack of oxygen content and acidity of the water are the bottom of the swamp due to weather changes. The purposes of the service activity is to provide solutions to the problems faced by tilapia farmers in Rowo Jombor by using the water spraying method to reduce the mortality rate of tilapia in the hope of increasing crop yields. The water used for spraying is taken from bore wells at the bottom of swamp. The results of service activities with the method of spraying water in cages have been proven to reduce tilapia morality from a mortality rate 50-70% to less than 5%. After the process of spraying water in tilapia rearing cages, farmers get additional profit because the mortality rate of fish decreases.